2010
DOI: 10.1182/blood-2009-12-257063
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative neoplasm induced by constitutive expression of JAK2V617F in knock-in mice

Abstract: The Jak2 V617F mutation is found in most classical BCR/ABL-negative myeloproliferative neoplasms (MPNs). Usually, heterozygosity of the mutation is associated with essential thrombocythemia (ET) and homozygosity with polycythemia vera (PV). Retrovirally transduced or transgenic animal models have shown that the mutation is sufficient for MPN development but that the level of expression is crucial for MPN phenotypes. Therefore we investigated the effect of an endogenous heterozygous expression of Jak2 V617F in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
123
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 14 publications
13
123
1
1
Order By: Relevance
“…These findings are also in consonance with functional differences between human PV and MF V617F mutant HSCs as detected in xenotransplant experiments. 18 Furthermore, the in vivo terminal expansion we demonstrate entirely corroborates the results in murine models [12][13][14] and human MPNs in vitro, where PV and ET patients demonstrated erythroid expansion compared with normal controls after long-term CD34 ϩ cell culture experiments. 19 We also demonstrate, using a novel PCR-based assay, that in individual patients the JAK2 V617F homozygous clone has a competitive advantage over the heterozygous clone and that the heterozygous clone does not significantly expand in vivo.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are also in consonance with functional differences between human PV and MF V617F mutant HSCs as detected in xenotransplant experiments. 18 Furthermore, the in vivo terminal expansion we demonstrate entirely corroborates the results in murine models [12][13][14] and human MPNs in vitro, where PV and ET patients demonstrated erythroid expansion compared with normal controls after long-term CD34 ϩ cell culture experiments. 19 We also demonstrate, using a novel PCR-based assay, that in individual patients the JAK2 V617F homozygous clone has a competitive advantage over the heterozygous clone and that the heterozygous clone does not significantly expand in vivo.…”
Section: Resultssupporting
confidence: 83%
“…2,[5][6][7][8][9] Recently, several groups have reported murine models of JAK2 V617F MPN. [10][11][12][13][14] However, the effects of JAK2 V617F expression on hematopoietic stem and progenitor cell (HSPC) homeostasis were not consistent, with the reports of Mullaly et al 14 and Li et al 12 suggesting a neutral or detrimental effect on HSPC compartment size and/or function, whereas Akada et al reported HSPC expansion. 11 In MPN patients, the consequences of JAK2 V617F expression for HSPC compartment homeostasis and later myeloid differentiation are largely unknown.…”
Section: Introductionmentioning
confidence: 94%
“…37 Jak2 V617F transgenic mice displayed ET-like phenotypes 38 and constitutive Stat5 phosphorylation was observed in Jak2 V617F knock-in mice with megakaryocyte hyperplasia and thrombocythemia. 39 In addition, our in-vitro study showed that activation of Jak signaling suppressed the endogenous caspase activation with increases in Mcl-1 and Bcl-xL. These findings suggest that increases in these anti-apoptotic proteins via activation of Jak signaling might be involved in the excessive megakaryocyte survival of ET patients.…”
Section: Discussionmentioning
confidence: 56%
“…17 Mouse models of JAK2V617F expressed from the endogenous genetic loci have provided important insights into JAK2 mutation biology. However, different models of the JAK2V617F mutation have resulted in strikingly heterogeneous phenotypes, with mice primarily developing an essential thrombocythemia phenotype in one model 19 as opposed to polycythemia in others, [20][21][22] and a phenotype that varied according to the ratio of mutant JAK2V617F to wild-type in another model. 23 Moreover, development of myelofibrosis also varied markedly.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Furthermore, these different models have produced conflicting results with regards to the impact of JAK2V617F on hematopoietic stem and progenitor cells, with different models suggesting a suppression, 19 no impact, 20 or expansion of HSCs 21,24 by the JAK2V617F mutation. One proposed explanation for this heterogeneity is that it relates to expression of human 19 versus murine [20][21][22] forms of the JAK2 protein. 4 However, understanding the impact of JAK2 mutation on human hematopoiesis is difficult in MPNs in which the JAK2 mutation may be present in only a subclone that may also have acquired multiple additional and heterogeneous genetic hits.…”
Section: Introductionmentioning
confidence: 99%